Recycling behaviour among university student: the determining factors / Wan Aisyah Wan Abd Aziz and Wan Alya Farisya Wan Amran - Wan Abd Aziz, Wan Aisyah; Wan Amran, Wan Alya Farisya (2022)
This study conducted among the university students to understand their behaviour in recycling activity and investigate more on the determinant factors influencing their behaviour. Malaysia recycling practices are still at low stages even though the government has initiated many recycling programs to increase citizens' awareness of solid waste management. Population of the young generation is quite significant in defining the future of solid waste management. It is vital to know the recycling behaviour among them and their awareness towards recycling activities. The researchers found a gap from the previous study as little studies were conducted to examine incentive as another independent variable. Thus, the determinant factors in this study were adopted from the Theory of Planned Behaviour (Attitudes, Subjective norms and Perceived Behavioural Control) and also incentives. To answer the research question, a quantitative method was employed whereby a total of 400 university students from Universiti Teknologi Mara Kampus Seremban 3 and Universiti Sultan Zainal Abidin Kampus Gong Badak were involved. The research design of this study is cross-sectional design where the one-shot questionnaire was distributed online. Finding of this study shows that (95.5%) university students are aware about the importance of recycling. There is no difference in recycling behaviour among university students based on type of university (p=0.679, p>0.05) and age (p=0.992, p>0.05). All variables, attitudes (r=0.502,p=0.00), subjective norms (r=0.664, p=0.00), perceived behavioural control (r=0.557,p=0.00) and incentives (r= 0.242,p=0.00) have a significant relationship with the recycling behaviour among the university students. Subjective norm is the main determinant factor influence on the recycling behaviour of university students (β = 0.421, p = 0.000). Based on the discussion on the findings, this study proposed several recommendations such as universities implementing the recycling campaign, the government to make some improvement in the current recycling program and campaign, universities to implement the incentive program and lastly to provide more recycling bins in the university area and public area.